OPTIMIZING CAPITAL STRUCTURE IN INCREASING COMPANY VALUE IN THE TELECOMMUNICATION INDUSTRY IN INDONESIA - Nurjanna Ladjin (Adisam Publisher, 2025)
This research focuses on the analysis of capital structure optimization in increasing company value in the telecommunications industry in Indonesia. The main objective of this research is to identify and analyze the impact of capital structure composition on company value, taking into account the specific dynamics of the telecommunications industry, which include market competition, regulation, technological developments, and consumer demand. Through literature research methods, this research collects and analyzes relevant previous studies, industry reports, company financial data, as well as theories related to capital structure and company value. The research results show that optimizing the capital structure through strategic debt and equity proportions can maximize company value. This is due to the company's ability to take advantage of lower debt costs, tax effects, and increased financial flexibility. Apart from that, this research also found that adapting to changes in the business environment quickly and adopting the latest technology are key factors in supporting the optimization of capital structure. This research provides important insights for stakeholders in the telecommunications industry and offers strategic recommendations for increasing company value through appropriate capital structure decisions.